International Association of Dental Traumatology guidelines for the management of traumatic dental injuries: 3. Injuries in the primary dentition. Issue 4 (20th July 2020) - Day, Peter F.; Flores, Marie Therese; O'Connell, Anne C.; Abbott, Paul V.; Tsilingaridis, Georgios; Fouad, Ashraf F.; Cohenca, Nestor; Lauridsen, Eva; Bourguignon, Cecilia; Hicks, Lamar; Andreasen, Jens Ove; Cehreli, Zafer C.; et al.
Abstract: Traumatic injuries to the primary dentition present special problems that often require far different management when compared to that used for the permanent dentition. The International Association of Dental Traumatology (IADT) has developed these Guidelines as a consensus statement after a comprehensive review of the dental literature and working group discussions. Experienced researchers and clinicians from various specialties and the general dentistry community were included in the working group. In cases where the published data did not appear conclusive, recommendations were based on the consensus opinions or majority decisions of the working group. They were then reviewed and approved by the members of the IADT Board of Directors. The primary goal of these Guidelines is to provide clinicians with an approach for the immediate or urgent care of primary teeth injuries based on the best evidence provided by the literature and expert opinions. The IADT cannot, and does not, guarantee favorable outcomes from strict adherence to the Guidelines; however, the IADT believes their application can maximize the probability of favorable outcomes.